2010
DOI: 10.1088/1674-1056/19/10/107501
|View full text |Cite
|
Sign up to set email alerts
|

Glassy phase and thermodynamics for random field Ising model on spherical lattice in magnetic field

Abstract: Phase diagram and thermodynamic parameters of the random field Ising model (RFIM) on spherical lattice are studied by using mean field theory. This lattice is placed in an external magnetic field (B). The random field (h i ) is assumed to be Gaussian distributed with zero mean and a variance ⟨The free energy (F ), the magnetization (M ) and the order parameter (q) are calculated. The ferromagnetic (FM) spin-glass (SG) phase transition is clearly observed. The critical temperature (T C ) is computed under a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…. This result agrees with those obtained by [35,36]. Because they found that a finite external field removes sharp phase transitions by…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…. This result agrees with those obtained by [35,36]. Because they found that a finite external field removes sharp phase transitions by…”
Section: Resultssupporting
confidence: 93%
“…The maximum of the peak lowers with increasing B. This result agrees with that obtained by Bannora et al [36] as well as agrees with that obtained by Ismail [37]. He found that real and imaginary parts of the dynamic susceptibility display maxima at C T T = .…”
Section: Resultssupporting
confidence: 91%